Respuesta :

g(x) = 2x^2 - 11x 
g(-1) = 2(-1)^2 - 11(-1) 
g(-1) = 2(1) - (-11) 
g(-1) =2 + 11 = 13

Answer: [tex]g(-1) = 13[/tex]

Step-by-step explanation:

The given function : [tex]g(x) = 2x^2 - 11x[/tex]

To find : g(-1)

i.e . To find the value of g(x) at x= -1.

For that we substitute x = -1 in the given function , then we have

[tex]g(-1) = 2(-1)^2 - 11(-1)[/tex]

[tex]\Rightarrow\ g(-1) = 2(-1\times-1) + 11\ \ [\because (-)(-)=(+)][/tex] [tex]\Rightarrow\ g(-1) = 2(1) + 11[/tex]

[tex]\Rightarrow\ g(-1) = 2+ 11[/tex]

[tex]\Rightarrow\ g(-1) = 13[/tex]

Therefore , the value of  [tex]g(-1) = 13[/tex] .